A A LITERATURE REVIEW OF SETTLEMENT LAND TRENDS (PAST, PRESENT, AND FUTURE) BASED ON ENGLISH-LANGUAGE ARTICLES INDEXED IN THE WEB OF SCIENCE DATABASE FROM 2014 TO 2023 - Abdurakhimova, Mokhigul (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This review explores the past, current, and future trends of settlement lands by analyzing papers indexed in the Web of science database published in English between 2014 and 2023. Settlement lands, which involves systematically measuring, recording, and analyzing land use, land cover, and land-related resources, is crucial for managing land resources sustainably. This review synthesizes findings from a range of studies, highlighting significant advancements, challenges, and evolving methodologies in Settlement lands. The analysis identifies key trends in the use of remote sensing technologies, Geographic Information Systems (GIS), and spatial data analytics, which have enhanced settlement lands practices. It also examines the growing importance of environmental sustainability, land degradation monitoring, and policy implications. In addition, it is necessary to scientifically and rationally guide rural settlements to agglomerate appropriately to improve the utilization efficiency of land resources and public service resources.